Staged Endovascular Repair of Aortic Coarctation followed by Double Valve Surgery - Avgerinos, Dimitrios V. (Aorta (Stamford), 2021)
We present a unique case of late diagnosis of coarctation of the aorta in an adult, presenting with congestive heart failure associated with severe aortic and mitral valve insufficiency. To minimize operative risk, staged endovascular repair of the coarctation was initially performed, followed by aortic valve replacement and mitral valve repair. Six months postoperatively, the 41-year-old patient remains completely asymptomatic.